Predicting Contribution in High Achieving Black and Latinx Youth: The Role of Critical Reflection, Hope, and Mentoring - Bowers, Edmond P.; Bolding, Candice W.; Rapa, Luke J.; Sandoval, Alexandra M. (Frontiers in Psychology, 2021)
Contemporary approaches to adolescent development are framed by positive youth development models. A key outcome of these models is that healthy and positively developing youth are more likely to contribute to their family, schools, and communities. However, little work on contribution and its antecedents has been conducted with youth of color. As high achieving youth of color often become leaders in their communities, it is important to consider malleable predictors of contribution within this population. Therefore, through a cross-sectional design, we examined the relations between youth critical reflection, hopeful future expectations, and mentoring relationship quality and youth contribution in a sample of 177 youth of color (60 % Black, 40% Latinx) attending an afterschool college preparation program at six sites around the U.S. Results indicated that youth critical reflection, hopeful future expectations, and mentoring relationship quality significantly predicted contribution. Exploratory analyses suggested that these relations were significant for Black youth but not Latinx youth. Implications of these findings for future scholarship are discussed.